KERJASAMA INDONESIA - FIJI DALAM BIDANG PENGOLAHAN DAN PENGEMBANGAN HASIL PERIKANAN PERIODE 2014-2016 - Rizky Ramadhan, - (2018)
This study discusses about the cooperation between Indonesia - Fiji in the field of processing and development of fishery products for the period 2014-2016. The lack of utilization in the fishery product sub-sector into a product in Fiji makes Indonesia see this as an opportunity to cooperate. This research focuses on how Indonesia - Fiji cooperation form in the processing and development of fishery products for the period 2014-2016. The Thinking Framework of this research uses bilateral cooperation theory and the concept of Technical Cooperation. This research uses descriptive method with qualitative approach type. The result of research of Indonesia - Fiji Cooperation in the field of processing and development of fishery products for the period 2014-2016 is a technical assistance which Indonesia sends experts to provide training in making processing and development of fishery products so it has more added value